Substandard and falsified medicine screening technologies - Lukas Roth; Kevin B. Biggs; Daniel K. Bempong (SpringerOpen, 2019)
Abstract Substandard and falsified medicine screening technologies are invaluable tools for post-marketing surveillance of medicine quality, particularly in low- and middle-income countries. National Regulatory Authorities and their partners leverage screening technologies to detect substandard and falsified medicines in the field and eliminate them from the medical product supply chain. An arsenal of different screening technologies has been developed to evaluate a variety of medicine quality attributes and performance characteristics, applying visual, physical and chemical analyses. Selecting the most effective screening technologies for a given quality challenge requires consideration of several practical, technical, and scientific factors, such as the type of medicines screened, the requirements of the screening technology, and the type of information needed. More widespread adoption of screening technologies will be facilitated by improved workforce development, technological advancements, and the development of a more robust supporting regulatory framework.